Peran Guru dalam Memotivasi Belajar Siswa Kelas V SDN 004 Sei Beberas Hilir Kecamatan Lubuk Batu Jaya Kabupaten Indragiri Hulu - Tri Widyastuti; Elpri Darta Putra (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
This study aims to find out how the teacher's role in motivating student learning besides the purpose of this study is to find out what obstacles are experienced by teachers in motivating student learning. This research uses a qualitative approach which is a case study. The data sources for this research are 1 class V teacher, 1 class IV teacher, and 2 students. Data collection techniques and instruments, in this case the researcher uses interviews and observations, focused data analysis using the Miles & Huberman model, namely data reduction, presentation, and drawing conclusions. There are four results obtained, the first is the teacher as a demonstrator, namely mastery of learning material by motivating student learning, the second is the teacher as a class manager, namely creating a learning climate in learning by motivating student learning, the third is the teacher as a mediator and facilitator, namely preparing the syllabus, lesson plans, and learning media, instill a spirit of student learning, and provide motivation in learning, and the fourth teacher as an evaluator is the evaluation results. Barriers experienced by teachers in motivating student learning include the teacher's lack of motivation or encouragement in learning due to the impact of covid-19, the role of the teacher becomes a much needed role in learning in motivating student learning so that students are more diligent and not lazy in learning